Analisis Kemampuan Pemecahan Masalah Word Problem PLSV - Hidayah, Siti Lilpatul Nurul Nur; Prayitno, Lydia Lia (Jurnal Tadris Matematika, 2023)
Problem-solving ability is a primary skill students should acquire in learning mathematics and is often connected to Adversity Quotient (AQ). This qualitative descriptive study describes the ability to solve PLSV problems regarding AQ (climbers, campers, and quitters) in 7th-grade students of SMP Negeri 21 Surabaya. Data were collected through questionnaires, tests, and interviews using instruments such as the AQ questionnaire sheet, Word Problem Solving Test (TPWP), questionnaires, and interview guidelines. The problem-solving ability in this study refers to the four stages of Polya's problem-solving ability including understanding the problem, planning, implementing, and evaluating. The results of this study showed that (1) the climbers subject was able to accomplish all of Polya's stages, (2) the campers subject, was able to accomplish three stages of Polya's problem solving, which were able to understand the problem, plan the problem solving, and carry out the problem-solving. Whereas, (3) the quitters subject, was unable to complete Polya's problem-solving stages as it showed that the subject was poorly understanding the problem, planning to solve the problem, implementing the solution plan, and incapable of looking back at problems that had been solved.